In Vitro Anti-cholinesterase Activity and Mass spectrometric Analysis of Curculigo orchioides Gaertn., Rhizome Extract. Issue 4 (3rd July 2020) - Pratap, G.K.; Rather, Suhail A.; Shantaram, Manjula
Abstract: Curculigo orchioides Gaertn, is commonly known as golden grass. Acetylcholinesterase is an enzyme involved in non-cholinergic and cholinergic activity in both the central and peripheral nervous systems, most of the AChE is found in a tetrameric form bound to neuronal cell membranes. The AChE induces amyloid-β fibril formation and forms very toxic AChE-Aβ complexes in the brain. The study aims to determine the anticholinesterase activity and chemical composition analysed by GC-MS, LC-MS, FT-IR, and HPTLC analysis in the methanolic extract of C. orchioides Gaertn rhizome. The in vitro anti-acetylcholinesterase activity was performed by bio-autograph and spectrophotometry. The methanolic extract of rhizome has better inhibition of the AChE enzyme in vitro experiments. These results might be useful in explaining the effect of the methanolic extract of the rhizome as an anti-acetylcholinesterase agent for the management of AD.